(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Culinary arts have undergone significant transformation in the modern era, blending traditional techniques with innovative approaches to meet the demands of a diverse and dynamic global audience. This paper explores the current trends in the culinary industry, including the rise of fusion cuisine, the integration of technology in food preparation, and the growing emphasis on sustainability and health-conscious dining.